Holistic integrated approach of designing a satellite town: Introducing theories of environmental parameters like pollution free, circular economy and sustainability - Disha Gupta; Anindita Bhattacharjee; Swati Bhargava; Shreyansh Gupta; Tania Das; Mansi Singh; Akshey Bhargava (International Journal of Architectural Design and Planning, 2025)
Urban regions are quite challenging to restore the quality of environment at the global level as well as posing serious threat to climatic changes. This fact is demonstrated on the grounds that around 70% of the carbon footprint is contributed from the urban sector. The authors of the present study have attempted to design a satellite town of population 50,000, partly to dilute the population density of main urban town and partly to make the satellite town as ideal to facilitate the migration of population from the main urban town. An effort has been made in the present study by the authors to address the issues of environmental degradation along with issues governing circular economy, sustainability, tourism hotspots, and perfect ecosystem. The satellite town is designed to infuse the concepts of urban air ventilation, balancing albedo effect, urban heat island effect, optimization between concreting and non-concreting urban surface area and adequate carrying capacity of roads. To develop satellite towns, urban forestry along with zoological parks and environmentally compatible residential towers with green roofs and solar panel coupled with parking spaces, schools, colleges, green parks, government institutions, hospitals, commercial areas, stadiums and water reservoirs to catch rainwater. Besides, water sports activity also has been designed along with an adventure club and circular toy train all along the periphery of the satellite town to attract the tourists. The solid waste and sewage generated shall be treated at the environmentally compatible site to transform into valuable resources, which shall be used for raising urban forestry and promoting green spaces. The reservoir water shall be treated with specified aquatic organisms. The present study aimed at holistic design in terms of overall environmental issues, circular economy, sustainability and tourism
Keywords: Environment; Ideal satellite town; Sustainability; circular economy; inclusive growth